2017
DOI: 10.1007/s00420-017-1231-1
|View full text |Cite
|
Sign up to set email alerts
|

Associations between common diseases and work ability and sick leave among health care workers

Abstract: PurposeThis study investigates whether common diseases, i.e., musculoskeletal diseases (MSD), cardiovascular diseases (CVD), mental disorders (MD), and respiratory diseases (RD), influence work ability and sick leave and whether lifestyle-related factors, and psychosocial and physical work-related factors are associated with low work ability and sick leave.MethodsIn a cross-sectional study among 8364 Dutch health care employees, self-reported information was acquired concerning common diseases, lifestyle-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
45
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 30 publications
(50 reference statements)
9
45
0
3
Order By: Relevance
“…To the best of our knowledge, no previous study has assessed the association between a multiple lifestyle risk index and sick leave in a general working population. However, two recent European studies [18,19] have assessed individual lifestyle risk factors and associations with sick leave among health care workers. A multi-cohort study found that lifestyle factors such as smoking and low physical activity were associated with sickness absence linked to respiratory disease [19], while a Dutch study did not find any significant associations between individual lifestyle factors and sick leave among persons with respiratory diseases [18].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To the best of our knowledge, no previous study has assessed the association between a multiple lifestyle risk index and sick leave in a general working population. However, two recent European studies [18,19] have assessed individual lifestyle risk factors and associations with sick leave among health care workers. A multi-cohort study found that lifestyle factors such as smoking and low physical activity were associated with sickness absence linked to respiratory disease [19], while a Dutch study did not find any significant associations between individual lifestyle factors and sick leave among persons with respiratory diseases [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, two recent European studies [18,19] have assessed individual lifestyle risk factors and associations with sick leave among health care workers. A multi-cohort study found that lifestyle factors such as smoking and low physical activity were associated with sickness absence linked to respiratory disease [19], while a Dutch study did not find any significant associations between individual lifestyle factors and sick leave among persons with respiratory diseases [18]. Unlike the present study, however, these studies did not specify which respiratory diseases were under investigation, and did not assess the strength of possible interactions with lifestyle factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If workers are not provided with favourable working conditions or too high requirements are set [6], then in the course of time, stress and emotional overload can be observed, which may have an impact on employees' ability. Thereby, the studies mostly have been focused on the impact of various socio-demographic and psychosocial risks [7,8], workload [9] shift/night work [10], and the health status of personnel [9,11,12] on the medical staff work abilities.…”
Section: Introductionmentioning
confidence: 99%